(untitled) (World Bulletin of Public Health, 2024)
The literature and our own data on modern methods of surgical treatment and clinical and immunologically based methods for choosing the prevention of purulent-septic complications in patients with liver echinococcosis , corresponding to the principles of evidence-based medicine, are summarized. Along with this, new algorithms for diagnostic and treatment tactics for uncomplicated and complicated forms of hydatid echinococcosis of the liver are described in detail.